A more radical human resource development: the time is now. Issue 4 (8th August 2019) - Collins, Joshua C.
ABSTRACT: The world is changing and so must human resource development (HRD). A cursory review of the scholarship in the four journals sponsored by the Academy of HRD revealed less than 10% of our discipline's research explicitly focuses on the experiences of women, LGBTQ (lesbian, gay, bisexual, transgender, and queer) people, millennials, people of colour, or immigrants and expatriates, and yet we know these groups have an increasing presence and impact on our organizations. The purpose of this essay is to amplify a call to action for radical change and to reiterate the imminent need for HRD to shift agendas in order to keep up.